Knowing the Description of the Role of Anatomy Fun Game on the Anatomy Learning Process of FKIK Ukrida Students - Handy Winata; Yvonne Marthina; Kevin Austro Kasi (Jurnal MedScientiae, 2023)
Anatomy is a basic science in the world of medicine. Relations with surrounding structures. There is so much material that makes it difficult for students to understand and memorize Anatomy material, and that is why they are friends of Anatomy at Krida Christian University. Discourse tries a learning method to assist students in learning by making a Game Base Learning application, namely Anatomy Fun Game which is an application that aims to assist students in preparing to take the Anatomy practicum exam, helping students in memorizing body Anatomy, and the Anatomy Fun Game application can be tried repeatedly. The design of this study was an analytic study using a retrospective time technique in data collection using a recap sample of basic cardiovascular Anatomy practicum values block 8 Class of 2015-2018. The percentage of the average grade of 2015 was 46.92, the average grade of 2016 was 32.44, the average grade of 2017 was 45.34 and the average grade of 2018 was 59.20 so that the application of Anatomy fun game (AFG) to the learning process quite satisfactory, this happened because the average grade of the 2017-2018 class was higher than the 2015-2016 class.